The Effect of Soaking Period on Chemical Quality of Gelatin Derived From Broiler Leg Skin - Joka, Elen Rosalia; Hafid, H.; Saili, T. (Proceeding INTERNATIONAL SEMINAR IMPROVING TROPICAL ANIMAL PRODUCTION FOR FOOD SECURITY)
Gelatin is usually used for the healthcare industry, photographic industry, and food industry.Hoee, a the gelati ee still ipoted fo aoad that ot suel halal, so it necessary toproduce our own gelatin. The product of gelatin this experiment used 2%NaOH with differentsoaking periods. The objective of this experiment was to determine the quality base-based gelatinproduced from the skin of broiler legs. Completely randomized design with three treatment ofsoaking periods (1 day, 2 day and 3 day)used in this experiments with three replications. Variablemeasured were pH, water content, fat and inorganic material (ash). Data obtain were analyzed usingvariance analysis and different between treatments were analyzed using multiple range Duncan test.The result showed that periods did not significantly affect the quality of gelatin derived from the skinof broiler legs.